Anthropogenic and climate‐driven water depletion in Asia - Shuang Yi; Wenke Sun; Wei Feng; Jianli Chen (Geophysical Research Letters)
Abstract Anthropogenic depletion of terrestrial water storage (TWS) can be alleviated in wet years and intensified in dry years, and this wet/dry pattern spanning seasons to years is termed climate variability. However, the anthropogenic and climate‐driven changes have not been isolated in previous studies; thus, the estimated trend of changes in TWS is strongly dependent on the study period. Here we try to remove the influence of climate variability from the estimation of the anthropogenic contribution, which is an indicator of the environmental burden and important for TWS projections. Toward this end, we propose a linear relationship between the variation in water storage and precipitation. Factors related to the sensitivity of water storage to precipitation are given to correct for the climate variability, and the anthropogenic depletion of terrestrial water and groundwater in Asia is estimated to be −187 ± 38 Gt/yr and −100 ± 47 Gt/yr, respectively.